Targeted albumin-based nanoparticles for delivery of amphipathic drugs - Xu, Rongzuo (2011)
We report the preparation and physical and biological characterization of human serum albumin-based micelles of approximately 30 nanometers diameter for the delivery of amphipathic drugs, represented by doxorubicin. The micelles were surface conjugated with cyclic RGD peptides to guide selective delivery to cells expressing the alpha v/beta 3 integrin. Multiple poly(ethylene glycol)s (PEGs) with molecular weight of 3400 daltons were used to form a hydrophilic outer layer, with the inner core formed by albumin conjugated with doxorubicin via disulfide bonds. Additional doxorubicin was physically adsorbed into this core to attain a high drug loading capacity, where each albumin was associated with about 50 doxorubicin molecules. The formed micelles were stable in serum but continuously released doxorubicin when incubated with free thiols at concentrations mimicking the intracellular environment. When incubated with human melanoma cells (M21+) that express the alpha v/beta 3 integrin, higher uptake and longer retention of doxorubicin was observed with the RGD-targeted micelles, than in the case of untargeted control micelles, or free doxorubicin. Consequently the RGD-targeted micelles manifested cytotoxicity at lower doses of drug than control micelles or free drug.